The role of immune checkpoints PD-1 and CTLA-4 in cardiovascular complications leading to heart failure - Huang, Shoulian; Kang, Yu; Liu, Ting; Xiong, Yan; Yang, Zixuan; Zhang, Qing (Frontiers in Immunology, 2025)
Immune checkpoints, such as PD-1 and CTLA-4, are crucial regulators of immune responses, acting as gatekeepers to balance immunity against foreign antigens and self-tolerance. These checkpoints play a key role in maintaining cardiac homeostasis by preventing immune-mediated damage to critical organs like the heart. In this study, we explored the involvement of PD-1 and CTLA-4 in cardiovascular complications, particularly atherosclerosis and myocarditis, which can lead to heart failure. We conducted a comprehensive analysis using animal models and clinical data to assess the effects of immune checkpoint inhibition on cardiac function. Our findings indicate that disruption of PD-1 and CTLA-4 pathways exacerbates myocardial inflammation, accelerates atherosclerotic plaque formation, and promotes the development of heart failure. Additionally, we observed that immune checkpoint inhibition in these models led to increased infiltration of T lymphocytes, higher levels of pro-inflammatory cytokines, and enhanced tissue damage. These results suggest that PD-1 and CTLA-4 are critical in preserving cardiac health, and their inhibition can result in severe cardiovascular toxicity. Our study emphasizes the need for careful monitoring of cardiovascular health in patients undergoing immune checkpoint inhibitor therapies.